Penerapan Pembiasaan Literasi dalam Meningkatkan Minat Baca Peserta Didik di Sekolah Dasar Negeri 095205 Parbalokan - Hartono Sinaga (Journal on Education, 2023)
The purpose of this study was to find out literacy habituation in increasing students' interest in reading at State Elementary School 095205 Parbalokan. The focus of this research: 1) How to apply the school literacy movement at the habituation stage, 2) How to apply the school literacy habituation at the development stage, 3) How to apply the school literacy habituation at the learning stage. This study uses a qualitative approach and a type of phenomenological study. Subject handling methods using purposive and snowball. Methods of data collection using observation, interviews, and documentation, and data analysis using an interactive model with the steps of data collection. compaction, presentation of data, drawing conclusions and verification. Test the validity of the data using source and method triangulation. The results of this study indicate: First, the habituation stage is the activity of reading 15 minutes aloud or silently. Second, the development stage, namely reading 15 minutes before the lesson. Third, the learning stage that has been used in learning all subjects. Reading strategies used to improve students' understanding of reading in all subjects. Activities to respond to reading in the form of oral, written, artistic, craft and other activities in accordance with students' literacy activities. Learning takes place in the school library, classroom reading corner, school reading area and others. Academic awards consider student costs.